2017
DOI: 10.15517/rbt.v65i2.23903
|View full text |Cite
|
Sign up to set email alerts
|

Morfología funcional del fitoplancton en un lago de alta montaña tropical: Lago de Tota (Boyacá-Colombia)

Abstract: Functional morphology of phytoplankton in a tropical high mountain lake: Tota Lake (Boyacá-Colombia). Functional morphology corresponds to adaptive responses to changes in the environment. In phytoplankton, traits such as the development of mucilage, oil vesicles, filaments and variation in the surface/volume ratio, allow algae to deal with sedimentation, optimizing light and nutrient uptake. The aim of this research was to evaluate the relationship between traits and variation in physical and chemical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
2
0
6
Order By: Relevance
“…The planktonic organisms identified in this study coincide with information recorded for other tropical mountain (Gaviria, 1989;Donato, 1991;Gaviria, 1993;Donato et al, 1996;Donato, 2010;Aranguren-Riaño et al, 2011;Muñoz-López et al, 2017) and lowland lakes (Duque & Núñez-Avellaneda, 2000;Pinilla, 2005;Barón-Rodríguez et al, 2006;Sala et al, 2008;Álvarez, 2010;Jaramillo-Londoño & Pinto-Coelho, 2010;Rivera et al, 2010;Andrade-Sossa et al, 2011;Jaramillo-Londoño & Aguirre-Ramírez, 2012;Aguirre-Ramírez, 2014;Sala et al, 2015) of Colombia. The greatest phytoplankton richness was found for the phyla Charophyta, Bacillariophyta, and Chlorophyta; this was possibly due to these species constituting the greatest percentage of species in lentic systems, despite differences in the environmental characteristics of mountain and lowland lakes (Donato et al, 1996;Canosa y Pinilla, 2007;Donato, 2010;Alba-M et al, 2011;Osorio-Ávila & Manjarres-García, 2015).…”
Section: Plankton Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…The planktonic organisms identified in this study coincide with information recorded for other tropical mountain (Gaviria, 1989;Donato, 1991;Gaviria, 1993;Donato et al, 1996;Donato, 2010;Aranguren-Riaño et al, 2011;Muñoz-López et al, 2017) and lowland lakes (Duque & Núñez-Avellaneda, 2000;Pinilla, 2005;Barón-Rodríguez et al, 2006;Sala et al, 2008;Álvarez, 2010;Jaramillo-Londoño & Pinto-Coelho, 2010;Rivera et al, 2010;Andrade-Sossa et al, 2011;Jaramillo-Londoño & Aguirre-Ramírez, 2012;Aguirre-Ramírez, 2014;Sala et al, 2015) of Colombia. The greatest phytoplankton richness was found for the phyla Charophyta, Bacillariophyta, and Chlorophyta; this was possibly due to these species constituting the greatest percentage of species in lentic systems, despite differences in the environmental characteristics of mountain and lowland lakes (Donato et al, 1996;Canosa y Pinilla, 2007;Donato, 2010;Alba-M et al, 2011;Osorio-Ávila & Manjarres-García, 2015).…”
Section: Plankton Analysissupporting
confidence: 87%
“…The species richness of phytoplankton in this work is high as compared with the results of other studies in tropical lakes. For example, Castaño et al, (2010) observed 25 phytoplankton species in Laguna Negra, Muñoz-López et al, (2017) reported 49 phytoplankton taxa in Lago de Tota, Jaramillo-Londoño & Aguirre-Ramirez (2012) recorded 74 phytoplankton species in the Ciénaga de Ayapel, Pava et al, (2006) reported 58 in the Ciénaga de San Silvestre. However, Donato et al, (2010) found a higher species richness than our studie, they identified 142 phytoplankton species in 20 tropical mountain lakes distributed along the three Andean Cordilleras.…”
Section: Plankton Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Según Mihaljević et al (2015) las condiciones bióticas y abióticas de las planicies de inundación están estrechamente ligadas a los períodos hidroclimáticos. En el presente estudio, la variación de las condiciones físicas y químicas durante el período comprendido resultó en cambios en la distribución temporal de los organismos y biovolumen representado en los diferentes GFBM, lo cual vislumbra cambios importantes en el sistema y en la respuesta de la comunidad del fitoplancton (Muñoz-López et al, 2017).…”
Section: Discussionunclassified
“…Diversos autores han concluido que el empleo de la morfología funcional permite revelar cambios asociados a la ecología del fitoplancton en ecosistemas acuáticos con diferentes tensores y características ambientales (Lins et al, 2017;Segura et al, 2018;Amorim et al, 2019;Kruk et al, 2017;Muñoz-López et al, 2017). Algunos estudios realizados en sistemas inundables han sido desarrollados en el lago de inundación brasilero `Batata´ y en la planicie de inundación del rio Danubio, los cuales han concluido que las propiedades físicas del medio, así como su dinámica pulsátil son altamente determinantes sobre las estrategias o asociaciones de los grupos funcionales encontrados (Mihaljević et al, 2015;Muñoz-López et al, 2017). En lagos de inundación con una columna de agua mezclada, somera y turbia, como la Ciénaga de Ayapel, predominan organismos de mayor tamaño, altos volumen y razón S/V, adaptados a muchas perturbaciones físicas y tolerantes a poca luz (Hernández-Atilano et al, 2012).…”
Section: Introductionunclassified